MEASURING COMMUNITY SATISFACTION IN LOCAL AUTHORITY: IMPORTANT SATISFACTION ANALYSIS - Budhi Suparningsih; Harry Indratjahyo; Suharto (Krisnadwipayana International Journal of Management Studies, 2021)
Local authority has the imperative rules to obtain community satisfaction through its performance. Quality services delivered to community driving prosperous local authority to delight community. Therefore, this research attempt to develop framework on community satisfaction through service quality dimensions. Important satisfaction analysis is deployed to measure community satisfaction towards service quality provided by local authority. The gap from this analysis enables to cater the level of importance and satisfaction of service quality provided by local authority. This method proposed in this study facilitates local authority to perform service excellence for the community.